Decontamination of fresh and minimally processed produce - Gomez-Lopez, Vicente M. (Wiley-Blackwell, 2012)
Attempts to provide safer and higher quality fresh and minimally processed produce have given rise to a wide variety of decontamination methods, each of which have been extensively researched in recent years. Decontamination of Fresh and MinimallyProcessed Produce is the first book to provide a systematic view of the different types of decontaminants for fresh and minimally processed produce. By describing the different effects - microbiological, sensory, nutritional and toxicological